Lipoprotein X Causes Renal Disease in LCAT Deficiency. - Alice Ossoli; Edward B Neufeld; Seth G Thacker; Boris Vaisman; Milton Pryor; Lita A Freeman; Christine A Brantner; Irina Baranova; Nicolás O Francone; Stephen J Demosky; Cecilia Vitali; Monica Locatelli; et al. (PLoS ONE)
Human familial lecithin:cholesterol acyltransferase (LCAT) deficiency (FLD) is characterized by low HDL, accumulation of an abnormal cholesterol-rich multilamellar particle called lipoprotein-X (LpX) in plasma, and renal disease. The aim of our study was to determine if LpX is nephrotoxic and to gain insight into the pathogenesis of FLD renal disease. We administered a synthetic LpX, nearly identical to endogenous LpX in its physical, chemical and biologic characteristics, to wild-type and Lcat-/- mice. Our in vitro and in vivo studies demonstrated an apoA-I and LCAT-dependent pathway for LpX conversion to HDL-like particles, which likely mediates normal plasma clearance of LpX. Plasma clearance of exogenous LpX was markedly delayed in Lcat-/- mice, which have low HDL, but only minimal amounts of endogenous LpX and do not spontaneously develop renal disease. Chronically administered exogenous LpX deposited in all renal glomerular cellular and matrical compartments of Lcat-/- mice, and induced proteinuria and nephrotoxic gene changes, as well as all of the hallmarks of FLD renal disease as assessed by histological, TEM, and SEM analyses. Extensive in vivo EM studies revealed LpX uptake by macropinocytosis into mouse glomerular endothelial cells, podocytes, and mesangial cells and delivery to lysosomes where it was degraded. Endocytosed LpX appeared to be degraded by both human podocyte and mesangial cell lysosomal PLA2 and induced podocyte secretion of pro-inflammatory IL-6 in vitro and renal Cxl10 expression in Lcat-/- mice. In conclusion, LpX is a nephrotoxic particle that in the absence of Lcat induces all of the histological and functional hallmarks of FLD and hence may serve as a biomarker for monitoring recombinant LCAT therapy. In addition, our studies suggest that LpX-induced loss of endothelial barrier function and release of cytokines by renal glomerular cells likely plays a role in the initiation and progression of FLD nephrosis.